Strengthening Governance in Islamic Early Childhood Education through the Halal Business Model Canvas: Evidence from Tadika Tahfiz Nur Furqan, Kedah, Malaysia - Fidia Putri; Rahmayati Rahmayati (Al-Abshar: Journal of Islamic Education Management, 2026)
lamic early childhood education institutions face increasing challenges in establishing sustainable, accountable, and Sharia-compliant governance while responding to growing demands for high-quality educational services. Existing governance models generally emphasize administrative and financial management, with limited attention to integrating strategic management frameworks and halal principles within Islamic educational institutions. This study aims to analyze the implementation of the Halal Business Model Canvas (HBMC) as a strategic governance framework at Tadika Tahfiz Nur Furqan, Kedah, Malaysia. A descriptive qualitative approach was employed, with data collected through semi-structured interviews, participatory observations, and document analysis. The findings were analyzed using the nine components of the Business Model Canvas—customer segments, value proposition, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure—integrated with Islamic principles of halal governance. The results demonstrate that the HBMC strengthens institutional governance through transparent financial management, trustworthy resource administration, strategic partnerships, effective parent communication, and educational services grounded in Islamic values. This study contributes to the advancement of Islamic educational management by proposing the Halal Business Model Canvas as a strategic governance model for Islamic early childhood education institutions. It also offers practical recommendations for enhancing institutional sustainability, managerial professionalism, and Sharia-based educational quality in contemporary Islamic education.